analisis sistem pelaksanaan lelang terhadap pendaptan asli daerah (PAD) di tempat pelelangan ikan (TPI) palabuhanratu - diponegoro, muhammad (COMPETITIVE, 2023)
Diponegoro (1630611112) Muhammadiyah University of Sukabumi. Analysis of the Auction Implementation System for Regional Original Revenue (PAD) at the Fish Auction Place (TPI) Palabuhanratu (Supervisors Deni Iskandar Z, M.AK., M.M. and Ade Sudarman, S.E., M.M)This study was made to find out the analysis of the auction system for Regional Original Revenue (PAD) at the Fish Auction Place (TPI) Palabuhanratu. This research was made using a qualitative method with a descriptive approach. The subject of this research is the Fish Auction Place (TPI) Palabuhanratu. While the objects of this research are fishermen, baskets and employees of TPI Palabuhanratu by covering the documents used, supporting records, and the establishment of an auction implementation system.The conclusions from the researchers of the fish auction system at TPI Palabuhanratu are carried out by auctioning the fish caught by fishermen and an open auction system in which the highest bidding results by baskets will win the auction. Each basket is required to deposit their capital with the TPI if they want to participate in the auction so that there is no delay in the payment process to fishermen. Although the fish auction system at TPI Palabuhanratu has not fully run optimally. Keywords: Fish Auction System, Local Revenue (PAD